2016
DOI: 10.3390/en9020114
|View full text |Cite
|
Sign up to set email alerts
|

A New Fluctuation Index: Characteristics and Application to Hydro-Wind Systems

Abstract: Hydro-wind system output fluctuations are the primary factors used to assess the effects of hydropower on power companies compensating for wind power intermittency. Considering that most fluctuation indices can only characterize one aspect of fluctuations, namely, the quantitative or contour variations, we present a new index that uses the standard deviation (SD) and rotation angle to detect the quantitative variations and contour changes, respectively. Herein, the new index is compared with commonly used indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…To our knowledge, this study is the first time a hybrid metric like C stab , combining information on complementarity and on CF, has been benchmarked against using average CF maps. The coefficient of variation itself [43][44][45]49], on which C stab is based, or alternative fluctuation indices [64] have been used before to quantify resource complementarities, but none of these works studied the implications of combining such metrics with information on CFs. The mathematical hybrid index for synergies presented by [65] goes in this direction, but it works optimally only if power output shapes are sinusoids, and its implications for RE potential estimation vis-à-vis using average CF maps were not studied.…”
Section: Locations Where Resources Are Complementarymentioning
confidence: 99%
“…To our knowledge, this study is the first time a hybrid metric like C stab , combining information on complementarity and on CF, has been benchmarked against using average CF maps. The coefficient of variation itself [43][44][45]49], on which C stab is based, or alternative fluctuation indices [64] have been used before to quantify resource complementarities, but none of these works studied the implications of combining such metrics with information on CFs. The mathematical hybrid index for synergies presented by [65] goes in this direction, but it works optimally only if power output shapes are sinusoids, and its implications for RE potential estimation vis-à-vis using average CF maps were not studied.…”
Section: Locations Where Resources Are Complementarymentioning
confidence: 99%
“…We employ the rotation angle, which is a sub-index of the Mei-Wang Fluctuation index (MWF) [35,36], to quantify the short-term fluctuations in the output. Comparisons in the previous study have suggested that the MWF, which combines a rotation angle and standard deviation, outperforms the commonly used methods (e.g., the Richards-Baker Flashiness index [37], the first-order difference, and the standard deviation) in characterizing fluctuation by incorporating not only the vertical variation but also the horizontal variation [35].…”
Section: Integration In Area Imentioning
confidence: 99%
“…In addition, λ i is the ratio of P SHP,exp i in the ith interval, which is the variable of this model and ranges from 0 to 1. The detailed definitions and calculations of the rotation angle can be found in a previous study [35].…”
Section: Integration In Area Imentioning
confidence: 99%
See 1 more Smart Citation
“…Hydropower is an important part of global renewable energy [1][2][3], which not only supports regional power supply but also helps to achieve decarburization targets [4,5]. Hydropower contributes to balance the power production variability of other kinds of renewable energy, like wind or solar power, because hydropower supply is relatively steadier and has good adaptability [6][7][8]. Thus, hydropower development is of significance and has great potential worldwide [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%